A current-responsive catalyst for enhancing the cracking of light alkanes to produce more low-carbon olefins and its application

By developing a current response catalyst for the recombination of MFI-type HZSM-5 molecular sieve with semiconductor-type metal oxide, the problem of insufficient conversion of light alkanes and selectivity of low-carbon olefins under mild conditions in the catalytic cracking field is solved, and efficient catalytic effect under mild conditions is achieved.

CN118668244BActive Publication Date: 2025-04-25INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410652687.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-04-25
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

The prior art has not yet effectively achieved light alkane conversion and low-carbon olefin selectivity under mild conditions in the field of catalytic cracking, and the naphtha steam cracking process has high energy consumption and large carbon emissions.

Method used

A current response catalyst made of MFI type HZSM-5 molecular sieve and semiconductor type metal oxide composite was developed, which was prepared by self-assembly, in situ hydrothermal method or physical mixing method, and had the ability to improve the conversion of light alkanes and selectivity of low carbon olefins under mild conditions.

Benefits of technology

Under the thermoelectric coupling conditions, the catalyst reduces the reaction temperature, improves the catalytic activity, inhibits the occurrence of side reactions, and significantly improves the selectivity of low-carbon olefins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a current-responsive catalyst and application for strengthening the cracking of light alkanes to produce more low-carbon olefins. The catalyst is mainly composed of MFI-type HZSM-5 molecular sieve and semiconductor-type metal oxide. The current-responsive catalyst of the present invention can realize the directional cracking of light alkanes under mild conditions (300-450°C) to prepare low-carbon olefins. Compared with the case without electric field under the same conditions, the conversion rate of light alkanes can be increased by 15-40%, and the selectivity of low-carbon olefins can be increased by 5-20%. The light hydrocarbon cracking process based on the above-mentioned current-responsive catalyst has the advantages of mild reaction conditions and high energy utilization, which solves the problems of high temperature (650-680°C) and high energy consumption in the traditional light hydrocarbon catalytic cracking process, and conforms to the concept of energy conservation, environmental protection and green.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petrochemical industry, and particularly relates to a current-responsive catalyst for strengthening cracking of light alkanes to produce more low-carbon olefins and an application thereof. Background Art

[0002] With the sustained and rapid development of my country's economy, the market demand for basic chemical raw materials such as ethylene and propylene continues to increase. The more mature process for industrial preparation of ethylene and propylene is naphtha steam cracking, which is an energy-intensive process with high energy consumption (reaction temperature above 800°C), large carbon emissions, and difficult product regulation.

[0003] The development of green and low-carbon chemical technology is of great significance to environmental protection and economic development. Low carbonization refers to replacing high-carbon emission coal or oil resources with carbon-free, low-carbon renewable energy or other new energy sources, as well as 2 The reduction and utilization of emissions will achieve low-carbon emissions in the entire process. The chemical process will be transformed to green and low-carbon, and the core equipment of the chemical industry will be electrified, ultimately achieving thermal power supply based on clean and renewable energy.

[0004] At present, catalytic technologies under mild conditions mainly include photocatalysis, plasma catalysis, electrocatalysis, biocatalysis, etc. Among them, thermoelectric coupled catalytic technology realized under the action of an external electric field is one of the research hotspots, and its core lies in the development of highly active current-responsive catalysts. Current-responsive catalysts are a type of catalytic material with suitable conductivity that can generate current under applied electric field conditions. Currently reported current-responsive catalysts include La / ZrO 2 、Ru / CeO 2 、Ni / SrTiO 3 etc., and exhibit excellent catalytic performance in the processes of synthetic ammonia, methane reforming, propane dehydrogenation, etc., such as: Pt-In / TiO 2 The catalyst can reduce the temperature of the propane dehydrogenation reaction from 600°C to 250°C, avoiding excessive energy consumption and forming a new green path for propane dehydrogenation.

[0005] The thermoelectric coupling process based on current-responsive catalysts is expected to make the reaction conditions of light hydrocarbon catalytic cracking milder and provide new ideas for the development of transformative catalytic cracking processes. However, the above technology has not been reported in the field of catalytic cracking. Summary of the invention

[0006] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.

[0007] The present invention provides a current-responsive catalyst for enhancing the cracking of light alkanes to produce more light olefins, which has the advantage of being able to significantly increase the light alkane conversion rate and light olefin selectivity under mild conditions.

[0008] The technical scheme adopted in this application is as follows: the current response catalyst developed to enhance the cracking of light alkanes to produce more low-carbon olefins is composed of MFI type HZSM-5 molecular sieve (SiO 2 / Al 2 O 3 The molar ratio includes (21, 25, 38, 50, 85, 120, 160, 200, 300 or 400): 1) and a semiconductor metal oxide are compounded, and the preparation method is: self-assembly method, in-situ hydrothermal method or physical mixing method.

[0009] The self-assembly method comprises the following steps:

[0010] (1) Add a certain amount of HZSM-5 as the core into anhydrous ethanol, stir evenly at room temperature, and then disperse by ultrasonication;

[0011] (2) dissolving a certain amount of polyvinyl pyrrolidone in anhydrous ethanol, slowly adding the solution to the solution in step (1), stirring evenly, and then ultrasonically treating;

[0012] (3) dissolving a certain amount of metal oxide precursor in anhydrous ethanol, slowly adding the mixture to the solution of step (2), ultrasonically treating the mixture, and then continuously stirring the mixture;

[0013] (4) slowly adding a certain amount of complexing agent to the solution of step (3), keeping stirring, and allowing to stand after the stirring is completed; and

[0014] (5) The solution after standing is centrifuged, washed and dried several times to obtain a preliminary solid product, which is then calcined to obtain a core-shell current responsive catalyst HZSM-5@MO x (M includes Ti, Ce or Sn).

[0015] In the above method, the stirring time in step (1) and step (2) is 0.5 to 8 hours, the ultrasonic power is 10 to 100 W, and the ultrasonic treatment time is 0.5 to 5 hours. More preferably, the stirring time is 0.5 to 5 hours, the ultrasonic power is 40 to 100 W, and the ultrasonic treatment time is 0.5 to 3 hours.

[0016] In the above step (2), the amount of polyvinyl pyrrolidone added is 1 to 10 wt % of HZSM-5; more preferably, the amount of polyvinyl pyrrolidone added is 2 to 8 wt % of HZSM-5.

[0017] The metal oxide precursor in step (3) of the above method is one or more of tetrabutyl titanate, isopropyl titanate, cerium nitrate, ammonium cerium nitrate, and tin tetrachloride pentahydrate, the mass ratio of the metal oxide precursor to HZSM-5 is (0.5-10):1, the stirring time is 0.5-12h, the ultrasonic power is 10-100W, and the ultrasonic treatment time is 0.5-5h; more preferably, the mass ratio of the metal precursor to HZSM-5 is (1-8):1, the stirring time is 0.5-10h, the ultrasonic power is 40-100W, and the ultrasonic treatment time is 0.5-3h.

[0018] The complexing agent described in step (4) of the above method is one or more of anhydrous ethanol aqueous solution or hexamethylenetetramine, the amount of the complexing agent used is 1 to 10 wt% of HZSM-5, and the standing time is 0.5 to 48 h; more preferably, the amount of the complexing agent used is 2 to 8 wt% of HZSM-5, and the standing time is 0.5 to 36 h.

[0019] In step (5) of the above method, the drying temperature is 80-150°C, the drying time is 6-24h, the roasting temperature is 400-700°C, the roasting time is 12-72h, and the heating rate is 2-10°C / min; more preferably, the drying temperature is 100-120°C, the drying time is 8-12h, the roasting temperature is 500-650°C, the roasting time is 12-48h, and the heating rate is 2-5°C / min.

[0020] The in-situ hydrothermal method comprises the following steps:

[0021] (1) Dissolve a certain amount of NaCl, polyethylene glycol 600, template agent and aluminum source in deionized water, perform ultrasonic treatment, stir evenly, dissolve a certain amount of silicon source in water, and quickly add;

[0022] (2) Then add a certain amount of semiconductor metal oxide MO x (M includes Ti, Ce or Sn) into the solution of step (1), ultrasonically treat, and pre-crystallize for a certain period of time at room temperature;

[0023] (3) Transferring the pre-crystallized solution to a hydrothermal reactor, and adopting a two-step crystallization method: first, hydrothermal crystallization at 50-150°C for 12-72h, and then hydrothermal crystallization at 100-200°C for 12-72h;

[0024] (4) cooling the product obtained in step (3), centrifuging, washing, drying, and calcining the product for multiple times to obtain an in-situ grown sodium-type current-responsive catalyst; and

[0025] (5) The sodium-type current-responsive catalyst was treated with 1 mol / L NH 4Cl solution was used for ion exchange, drying and calcination to obtain the hydrogen-type current response catalyst MO. x @HZSM-5 (M includes Ti, Ce or Sn).

[0026] In step (1) of the above method, the template agent is tetrapropylammonium hydroxide, the aluminum source is one or both of aluminum isopropoxide and aluminum nitrate nonahydrate, and the silicon source is tetraethyl silicate. The molar ratio of each substance is SiO 2 :Al 2 O 3 :TPAOH:Na 2 O:H 2 O=1:(0.01~0.02):(0.2~0.5):(0.02~0.05):(20~200); More preferably, SiO 2 :Al 2 O 3 :TPAOH:Na 2 O:H 2 O=1: (0.01~0.02): (0.2~0.3): (0.02~0.03): (50~150).

[0027] In step (2) of the above method, the semiconductor metal oxide MO x Anatase TiO 2 , rutile TiO 2 、CeO 2 or SnO 2 One or more of MO x The dosage is 1-8wt% of HZSM-5, and the pre-crystallization time is 6-72h; more preferably, MO x The dosage is 2-6 wt % of HZSM-5, and the pre-crystallization time is 12-48 h.

[0028] In steps (4) and (5) of the above method, the calcination conditions are a temperature of 450-800°C, a time of 3-12 hours, and a heating rate of 2-10°C / min; more preferably, the calcination temperature is 550-650°C, the calcination time is 3-6 hours, and the heating rate is 2-5°C / min.

[0029] In step (5) of the above method, the ion exchange conditions are: MO x @HZSM-5 and NH 4 The mass ratio of Cl solution was 1:10, the ion exchange temperature was 80 °C, the ion exchange time was 4 h, and the number of ion exchanges was 2 times.

[0030] The physical mixing method comprises the following steps:

[0031] HZSM-5 and semiconductor metal oxide (anatase TiO2 , rutile TiO 2 、CeO 2 or SnO 2 One or more of the above) are placed in deionized water according to a certain mass ratio, mechanically mixed under 10-100W ultrasonic conditions for 1-5h, and then centrifuged and dried to obtain a composite current responsive catalyst HZSM-5 / MO x (M includes Ti, Ce or Sn).

[0032] The present invention also provides an application of a current-responsive catalyst in catalyzing the cracking of light alkanes to produce low-carbon olefins. The application process mainly includes the following steps:

[0033] (1) Pressing the prepared current-responsive catalyst into tablets, sieving to 20-40 mesh, and taking 1.0 g of the catalyst into a fixed bed reactor equipped with electrodes;

[0034] (2) In N 2 In the atmosphere, the reactor was raised to the target temperature, direct current was applied, and stabilized for 2 hours; and

[0035] (3) A light alkane feedstock is introduced to start the reaction, and the product composition is analyzed online by gas chromatography.

[0036] In the application of the above-mentioned current-responsive catalyst, the catalytic cracking reaction of light alkanes to produce low-carbon olefins uses alkanes with a chain length of C4 to C10 as raw materials, N 2 As carrier gas, the space velocity of light alkanes is 10~80mmol / g / h,N 2 The flow rate is 5-60 mL / min, the cracking reaction temperature is 300-450°C, the DC voltage is 0-1000 V, the current is 0-3 A, and the power is 0-50 W; more preferably, the space velocity of the light alkane is 20-40 mmol / g / h, N 2 The flow rate is 10-50 mL / min and the power is 0-30 W.

[0037] Compared with the related art, the present invention has the following beneficial effects:

[0038] (1) The catalytic material prepared by the current-responsive catalyst synthesis method provided by the present invention introduces a conductive layer without destroying the topological structure of the HZSM-5 molecular sieve, and has current-responsive characteristics under the action of a direct current electric field; and

[0039] (2) The current-responsive catalyst provided by the present invention is used to catalyze the cracking of light alkanes to produce low-carbon olefins. Under thermoelectric coupling conditions, the reaction temperature is reduced, the catalytic activity is increased, the occurrence of side reactions is suppressed, and the selectivity of low-carbon olefins is increased.

[0040] Other aspects will be apparent upon reading and understanding the detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] none DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] Example 1

[0044] Core-shell current-responsive catalyst HZSM-5@TiO 2

[0045] (1) 1.5 g of HZSM-5 as the core was added to anhydrous ethanol, stirred at room temperature for 1 h, and then ultrasonically treated at 60 W for 1 h;

[0046] (2) dissolving 2 wt % polyvinyl pyrrolidone in anhydrous ethanol, slowly adding the solution to the solution in step (1), stirring evenly, and then ultrasonically treating at 60 W for 1 h;

[0047] (3) 6.39 g of tetrabutyl titanate was dissolved in anhydrous ethanol, slowly added to the solution of step (2), ultrasonically treated at 60W for 1 h, and then stirred for 5 h;

[0048] (4) slowly adding 2 wt % anhydrous ethanol aqueous solution to the solution in step (3), keeping stirring, and after the stirring is completed, standing for 12 hours; and

[0049] (5) The solution after standing was centrifuged and washed several times, and dried at 110°C for 10 h to obtain a preliminary solid product. The solid product was calcined at 600°C for 24 h to obtain a core-shell current responsive catalyst HZSM-5@TiO 2 .

[0050] Example 2

[0051] The core-shell current responsive catalyst HZSM-5@TiO was prepared by the same method and steps as in Example 1. 2 The difference is that the amount of polyvinyl pyrrolidone used in step (2) is 4 wt% of HZSM-5 to regulate the electrostatic effect on the surface of HZSM-5.

[0052] Example 3

[0053] The core-shell current responsive catalyst HZSM-5@TiO was prepared by the same method and steps as in Example 1. 2 , the difference is that the metal precursor in step (3) is isopropyl titanate.

[0054] Example 4

[0055] The core-shell current responsive catalyst HZSM-5@TiO was prepared by the same method and steps as in Example 1. 2 The difference is that the amount of anhydrous ethanol aqueous solution used in step (4) is 3wt% to regulate the hydrolysis rate of the titanium dioxide metal precursor.

[0056] Example 5

[0057] The core-shell current responsive catalyst HZSM-5@TiO was prepared by the same method and steps as in Example 1. 2 The difference is that the amount of anhydrous ethanol aqueous solution used in step (4) is 4 wt % to regulate the hydrolysis rate of the titanium dioxide metal precursor.

[0058] Example 6

[0059] The core-shell current responsive catalyst HZSM-5@TiO was prepared by the same method and steps as in Example 1. 2 , except that the standing time in step (4) is 24h.

[0060] Example 7

[0061] Core-shell current-responsive catalyst HZSM-5@CeO 2

[0062] (1) 1.5 g of HZSM-5 as the core was added to anhydrous ethanol, stirred at room temperature for 1 h, and then ultrasonically treated at 60 W for 1 h;

[0063] (2) dissolving 2 wt % polyvinyl pyrrolidone in anhydrous ethanol, slowly adding the solution to the solution in step (1), stirring evenly, and then ultrasonically treating at 60 W for 1 h;

[0064] (3) dissolving 1.8 g of cerium nitrate in anhydrous ethanol, slowly adding it to the solution in step (2), ultrasonically treating at 60W for 1 h, and then stirring continuously for 5 h;

[0065] (4) dissolving 1 g of hexamethylenetetramine in anhydrous ethanol, slowly adding the mixture to the solution of step (3), and stirring the mixture. After stirring, the mixture was allowed to stand for 12 h; and

[0066] (5) The solution after standing was centrifuged and washed several times, and dried at 110°C for 10 h to obtain a preliminary solid product. The preliminary solid product was calcined at 600°C for 24 h to obtain a core-shell current responsive catalyst HZSM-5@CeO 2 .

[0067] Example 8

[0068] The core-shell current responsive catalyst HZSM-5@CeO was prepared by the same method and steps as in Example 7. 2 The difference is that the amount of polyvinyl pyrrolidone used in step (2) is 4 wt% of HZSM-5 to regulate the electrostatic effect on the surface of HZSM-5.

[0069] Example 9

[0070] The core-shell current responsive catalyst HZSM-5@CeO was prepared by the same method and steps as in Example 7. 2 , the difference is that the metal oxide precursor in step (3) is ammonium cerium nitrate.

[0071] Example 10

[0072] The core-shell current responsive catalyst HZSM-5@CeO was prepared by the same method and steps as in Example 7. 2 , except that the mass of hexamethylenetetramine in step (4) is 1.8 g.

[0073] Embodiment 11

[0074] The core-shell current responsive catalyst HZSM-5@CeO was prepared by the same method and steps as in Example 7. 2 , except that the mass of hexamethylenetetramine in step (4) is 3.6 g.

[0075] Example 12

[0076] The core-shell current responsive catalyst HZSM-5@CeO was prepared by the same method and steps as in Example 7. 2 , except that the standing time in step (4) is 24h.

[0077] Embodiment 13

[0078] In-situ grown current-responsive catalyst TiO 2 @HZSM-5

[0079] (1) 0.3 g NaCl, 2.5 g polyethylene glycol 600, 5.625 g TPAOH, and 0.1 g aluminum nitrate nonahydrate were dissolved in deionized water, ultrasonically treated, and stirred evenly. 3.27 g tetraethyl silicate was dissolved in water and quickly added;

[0080] (2) Then add 2g rutile TiO 2 Add to the solution of step (1), perform ultrasonic treatment, and pre-crystallize at room temperature for 24 hours;

[0081] (3) The pre-crystallized solution was transferred to a hydrothermal reactor for two-step crystallization: first, hydrothermal crystallization at 80°C for 24 h, and then hydrothermal crystallization at 170°C for 36 h;

[0082] (4) The product obtained in step (3) was cooled, centrifuged and washed several times, dried at 110°C for 10 h, and calcined at 600°C for 4 h to obtain rutile TiO 2 @Na-ZSM-5; and

[0083] (5) TiO 2 @Na-ZSM-5 uses 1 mol / L NH 4 The Cl solution was stirred at 80 °C for 4 h for ion exchange, and after repeating twice, TiO 2 @NH 4 -ZSM-5, followed by drying at 110 °C for 10 h and calcination at 600 °C for 4 h to obtain rutile TiO 2 @HZSM-5.

[0084] Embodiment 14

[0085] The in-situ growth type current responsive catalyst TiO was prepared by the same method and steps as in Example 13. 2 @HZSM-5, the difference is that the aluminum source in step (1) is aluminum isopropoxide.

[0086] Embodiment 15

[0087] The in-situ growth type current responsive catalyst TiO was prepared by the same method and steps as in Example 13. 2 @HZSM-5, the difference is that the titanium source in step (2) is anatase TiO 2 .

[0088] Example 16

[0089] The in-situ growth type current responsive catalyst TiO was prepared by the same method and steps as in Example 13. 2 @HZSM-5, the difference is that the first crystallization time in step (3) is 36h.

[0090] Embodiment 17

[0091] The in-situ growth type current responsive catalyst TiO was prepared by the same method and steps as in Example 13. 2 @HZSM-5, the difference is that the second crystallization time in step (3) is 48h.

[0092] Embodiment 18

[0093] The in-situ growth type current responsive catalyst CeO was prepared by the same method and steps as in Example 13.2 @HZSM-5, the difference is that in step (2) MO x CeO 2 .

[0094] Embodiment 19

[0095] The in-situ growth current response catalyst SnO was prepared according to the same method and steps as in Example 13. 2 @HZSM-5, the difference is that in step (2) MO x SnO 2 .

[0096] Embodiment 20

[0097] Physical hybrid current responsive catalyst HZSM-5 / TiO 2

[0098] HZSM-5 and anatase TiO 2 According to the mass ratio m(TiO 2 :HZSM-5)=1:1 were placed in deionized water, mechanically mixed at 80W ultrasonic power for 3h, then centrifuged and dried at 110℃ for 10h to obtain the physical hybrid current response catalyst HZSM-5 / TiO 2 .

[0099] Embodiment 21

[0100] The physical mixed current response catalyst HZSM-5 / TiO was prepared by the same method and steps as in Example 20. 2 The difference is that TiO 2 It is rutile type.

[0101] Embodiment 22

[0102] The physical mixed current response catalyst HZSM-5 / TiO was prepared by the same method and steps as in Example 20. 2 , the difference is the mass ratio m(TiO 2 :HZSM-5)=1.5:1.

[0103] Embodiment 23

[0104] The physical mixed current response catalyst HZSM-5 / TiO was prepared by the same method and steps as in Example 20. 2 , the difference is the mass ratio m(TiO 2 :HZSM-5)=2:1.

[0105] Embodiment 24

[0106] The physical mixed current response catalyst HZSM-5 / CeO was prepared by the same method and steps as in Example 20. 2 , the difference is that MO x CeO 2 .

[0107] Embodiment 25

[0108] The physical mixed current response catalyst HZSM-5 / SnO was prepared by the same method and steps as in Example 20. 2 , the difference is that MO x SnO 2 .

[0109] Application Examples

[0110] A series of current-responsive catalysts obtained in Examples 1-25 were used to catalyze the cracking of light alkanes. The evaluation device used was a micro-electrode fixed-bed reactor. The specific process was as follows:

[0111] (1) Pressing the prepared current-responsive catalyst powder into tablets, sieving to 20-40 mesh, and taking 1.0 g of the catalyst into a micro-electrode fixed bed reactor;

[0112] (2) Controlling the carrier gas N 2 The flow rate was 40.0 mL / min under N 2 In the atmosphere, the reactor was heated to the set temperature, a direct current (0 / 5 W, 0 W represents no electric field, 5 W represents the power under the applied electric field) was applied, and the temperature was stabilized for 2 h; and

[0113] (3) Add light alkane feedstock to start the reaction, where the light alkane space velocity is 40 mmol / g / h. The product composition was analyzed online by gas chromatography, with sampling every 1 h.

[0114] The conversion rate and the selectivity of the main products are shown in Table 1 and Table 2. (In the table, "triene" includes ethylene, propylene and butene; "BTX" includes benzene, toluene and xylene)

[0115] Table 1 Performance of the current-responsive catalyst prepared in Example 1 in cracking n-hexane with / without electric field

[0116]

[0117]

[0118] Note: 0W represents no electric field, 5W represents the power under applied electric field

[0119] Table 2 Performance of the current-responsive catalyst prepared in Example 2 in the presence or absence of electric field for cracking n-octane

[0120]

[0121]

[0122] Note: 0W represents no electric field, and 5W represents the power under applied electric field.

Claims

1. An application of a current-responsive catalyst to crack light alkanes under the action of an electric field to produce more low-carbon olefins, wherein the low-carbon olefins include ethylene, propylene and butene, and by-produce benzene, toluene and xylene; the current-responsive catalyst is obtained by compounding an MFI-type HZSM-5 molecular sieve and a semiconductor-type metal oxide anatase-type TiO2, rutile-type TiO2, CeO2 or SnO2.

2. Application of the current-responsive catalyst according to claim 1 to crack light alkanes to produce more low-carbon olefins under the action of an electric field, wherein: The SiO2 / Al2O3 molar ratio of the MFI type HZSM-5 molecular sieve is 21, 25, 38, 50, 85, 120, 160, 200, 300 or 400.

3. Application of the current-responsive catalyst according to claim 1 to crack light alkanes to produce more low-carbon olefins under the action of an electric field, wherein: The composite method of the molecular sieve and the semiconductor metal oxide includes a self-assembly method, an in-situ hydrothermal method or a physical mixing method.

4. Use of the current-responsive catalyst according to claim 1 to crack light alkanes to produce more low-carbon olefins under the action of an electric field, wherein: The mass ratio of the semiconductor metal oxide to HZSM-5 is (0.5-10):

1.

5. Use of the current-responsive catalyst according to claim 1 to crack light alkanes to produce more low-carbon olefins under the action of an electric field, wherein: Direct current is used in the catalytic cracking process of light alkanes, with a voltage of 0 to 1000 V, a current of 0 to 3 A, and a power of 0 to 50 W.

6. Use of the current-responsive catalyst according to claim 1 to crack light alkanes to produce more low-carbon olefins under the action of an electric field, wherein: The catalytic cracking temperature of the light alkane is 300-450°C.

7. Use of the current-responsive catalyst according to claim 1 to crack light alkanes to produce more low-carbon olefins under the action of an electric field, wherein: The light alkanes are alkanes with a chain length of C4 to C10.